PENGARUH PENGGUNAAN METODE SIMULASI TERHADAP MINAT BELAJAR PENDIDIKAN KEWARGANEGARAAN PADA SISWA KELAS V SDN KOTAGEDE 3 YOGYAKARTA - Arifin Riyanto; Trisharsiwi Trisharsiwi (Universitas Sarjanawiyata Tamansiswa, 2018)
Abstract: The purpose of this study is to know descriptively the tendency of interest in civics of the fifth grade students in SDN Kotagede 3 Yogyakarta that use simulation method and do not use simulation method in the learning teaching process. Comparatively, this study is to know the difference of interest in civics in fifth grade at SDN Kotagede 3 Yogyakarta between using simulation method and without using the simulation method. This study included experimental research. The population and sample in this research are all fifth graders class, the consist 60 students. Data collection of this research uses observation techniques, documentation techniques, and questionnaire techniques. The result of descriptive research indicate that the tendency of study interest of the fifth grade students of elementary school of Kotagede 3 Yogyakarta which are taught using the simulation method is very high category with the mean of 72,77, while students are taught without using the simulation method included in high category with the mean of 66,33. In t-test obtained tcount = 3.798> ttable = 2,002 with p = 0,000, because tcount > ttableÂ and p<0.05 the hypothesis that is proposed can be accepted. Comparatively, there is difference is most significant of interest in learning civics of the fifth grade students in SDN Kotagede 3 Yogyakarta between students who is taught by using simulation method andÂ without using simulation method.